(untitled) (The Eurasia Proceedings of Educational and Social Sciences, 2019)
This paper investigates Lebanese high school biology teachers’ perceptions and practice of Conceptual Integration among different science subject areas in the biology class. Fifty Lebanese in-service high school teachers completed a questionnaire about their perceptions of conceptual integration. Then, ten of them participated in a focus group to discuss the implementation of Conceptual Integration through an activity presented in the grade 10 biology program. The findings show that although teachers acknowledge the importance of integrating physics and chemistry in their biology teaching, they avoid implementing Conceptual Integration. In addition, they lack the right knowledge about what Conceptual Integration is and how to approach it in their practice. The study shed the light on the urge to revisit the teacher education program at the Faculty of Education at the Lebanese University, at the pedagogical level to include Conceptual Integration as a main strategy to teach Sciences and at the content knowledge level to highlight the one paradigm of science that includes various science disciplines sharing the same features of the “nature of Science”.